(untitled) - Douglas, William O. (Bethesda, 1987)
Selections from the private papers of Justice William O. Douglas. Bold and controversial in his opinions, Justice Douglas exhibited these qualities in his correspondence as well
Keywords: Judges,Các thẩm phán; Thư từ; United States,Hoa Kỳ